Hepatorenal Syndrome: Physiology, Diagnosis and Management - Chmielewski, Joseph; Lewandowski, Robert J.; Maddur, Haripriya (Seminars in Interventional Radiology, 2018)
Individuals with end-stage liver disease are susceptible to a myriad of highly morbid complications, including hepatorenal syndrome (HRS). This specific type of renal dysfunction in patients with underlying liver disease occurs in pathophysiologically normal kidneys and is a result of renal vasoconstriction secondary to diminished renal blood flow in the setting of worsening hepatic dysfunction. Liver transplantation is curative; shortage of available organs limits access to this beneficial therapy. Medical management of HRS has demonstrated increasing promise. Transjugular intrahepatic portosystemic shunt creation has also been shown to be efficacious in enhancing transplant-free survival, although further study is advisable before widespread implementation of this strategy.
Keywords: hepatorenal syndrome; pathophysiology; TIPS; terlipressin